2016
DOI: 10.1371/journal.pone.0159174
|View full text |Cite
|
Sign up to set email alerts
|

Transferring Patients with Intracerebral Hemorrhage Does Not Increase In-Hospital Mortality

Abstract: IntroductionComprehensive stroke centers (CSCs) accept transferred patients from referring hospitals in a given regional area. The transfer process itself has not been studied as a potential factor that may impact outcome. We compared in-hospital mortality and severe disability or death at CSCs between transferred and directly admitted intracerebral hemorrhage (ICH) patients of matched severity.Materials and MethodsWe retrospectively reviewed all primary ICH patients from a prospectively-collected stroke regis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 28 publications
(15 reference statements)
0
5
0
Order By: Relevance
“…In patients with intracerebral hemorrhage, Vahidy et al observed no difference in functional outcomes and mortality between direct-admit and transferred patients. 30 Naval and Carhuapoma also saw no differences in in-hospital mortality rates between the patients with intracerebral hemorrhage who were directly admitted or transferred. 31 Holland et al showed that the mortality rate in transferred patients with spinal cord injury decreased in their study period, while the frequency of surgical management before transfer increased.…”
Section: In-hospital Mortalitymentioning
confidence: 87%
“…In patients with intracerebral hemorrhage, Vahidy et al observed no difference in functional outcomes and mortality between direct-admit and transferred patients. 30 Naval and Carhuapoma also saw no differences in in-hospital mortality rates between the patients with intracerebral hemorrhage who were directly admitted or transferred. 31 Holland et al showed that the mortality rate in transferred patients with spinal cord injury decreased in their study period, while the frequency of surgical management before transfer increased.…”
Section: In-hospital Mortalitymentioning
confidence: 87%
“…Illness severity, time-sensitive variables, and detailed information related to the transfer may be effect modifiers, and may have contributed to the outcomes of patients examined; due to limitations of the database, they could not be modelled, and should be investigated in future studies. The patient’s neurological status and intracranial haemorrhage as the reason for transfer, for example, have an effect on mortality but are not modeled here (11). Sixth, subgroup analysis would have been helpful to assess heterogeneity of treatment effect; however, relevant variables such as timing of the transfer and differences between the sending and receiving hospitals were not available in the database.…”
Section: Discussionmentioning
confidence: 99%
“…The assumption has been that IHT of critically ill patients will result in improved outcomes, and that the risks and costs of transportation are outweighed by the benefits (13). The risk-benefit ratio appears to strongly favor transfer for some conditions, such as acute coronary syndrome, stroke, and trauma (411), but the ratio is less clear (and often remains to be studied) for many others (12, 13). IHT has been shown to cause delays in administering timely treatments for sepsis, and there is recent concern that IHT could be a vector for nosocomial pathogens(14, 15).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it would be difficult to implement any of these ML algorithms at other institutions where the PACS software and CT imaging protocols for ICH patients may have subtle differences. Many critically ill ICH patients at larger academic centers are often transferred from smaller outside hospitals where the initial head CT was performed (Vahidy et al, 2016). A successful algorithm is one that can be implemented at both tertiary centers and smaller hospitals with differing software.…”
Section: Limitations and Future Directions For ML Algorithms In Cereb...mentioning
confidence: 99%